2009
DOI: 10.1029/2008jd011332
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of high‐frequency gravity waves generated by tropical deep convection: Case studies

Abstract: [1] High-frequency gravity waves generated by tropical deep convection play a major role in shaping the general circulation of the middle atmosphere. Special experiments were conducted to capture two convective events on 16 May and 5 June 2006 using VHF radar located at Gadanki (13.5°N, 79.2°E), a tropical Indian station. Control day observations were also made for necessary comparisons. Background wind and temperature information was obtained by GPS radiosonde flights launched from the same site. This work ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 64 publications
1
28
0
Order By: Relevance
“…In a few studies (Kumar, 2006(Kumar, , 2007Dhaka et al, 2002;Venkat Ratnam et al, 2008;Debashis Nath et al, 2009;Dutta et al, 2009;Leena et al, 2012a, b), possible sources in the troposphere for their generation are identified which include convection, wind shear and topography.…”
Section: Introductionmentioning
confidence: 99%
“…In a few studies (Kumar, 2006(Kumar, , 2007Dhaka et al, 2002;Venkat Ratnam et al, 2008;Debashis Nath et al, 2009;Dutta et al, 2009;Leena et al, 2012a, b), possible sources in the troposphere for their generation are identified which include convection, wind shear and topography.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the traditional hodograph analysis in fact can only be applied to study low-frequency GWs. Observational studies on lower-atmospheric medium-and high-frequency GWs (MHGWs) are mainly from only radiosonde at a tropical station (Leena et al, 2012b) and few radar observations at several limited sites (Dutta et al, 2009;Kuo et al, 2009, Leena et al, 2012b. Then, considering the long-term accumulations and extensive land distribution of radiosonde observations, in order to further understand the MHGWs in the lower atmosphere we need a feasible method to extract MHGW parameters from more radiosonde observations.…”
Section: S D Zhang Et Al: Spatial and Seasonal Variability Of Medimentioning
confidence: 99%
“…Alexander (1995) simulated squall lines, observing harmonics with a period of around 23-28 min in the troposphere and 12.8-7.8 min in the stratosphere, attributing them to the mechanical oscillator effect. Dutta et al (2009), have found significant periodicities between 8-15 min, 20-60 min, and 60-80 min in the troposphere between 5-10 and 10-15 km and 12.5-15 min, 15-18 min and 20-70 min bands in the lower stratosphere (LS) between 17-22 km. Numerical simulations performed by Beres et al (2004), showed that periods between 10 min and 100 min are observed.…”
Section: Introductionmentioning
confidence: 99%
“…Convective instability creates oscillatory displacements in the isentropic/isobaric surfaces and generates GWs that propagate vertically as a harmonic oscillator (Clark et al, 1986;Fovell et al, 1992;Alexander, 1995;Alexander and Holton, 1997;Lane and Reeder, 2001;Dhaka et al, 2002Dhaka et al, , 2003Kumar, 2006Kumar, , 2007Dutta et al, 2009). Based on two different convective events, Kumar (2007) studied the nonlinear interaction of GWs, finding periods of 28-12 min (35-15 min) in the troposphere and 21-8.4 min (26 min) in the lower stratosphere.…”
Section: Introductionmentioning
confidence: 99%